A Review of Tolerance and Safety Profiles of Long-Term Botulinum Neurotoxin Type A in Asian Patients with Hemifacial Spasm and Benign Essential Blepharospasm. (3rd September 2021) - Lai, Kenneth Ka Hei; Tsang, Alan; Kuk, Andrew K. T.; Ko, Callie K. L.; Chan, Edwin; Ko, Simon T. C.
ABSTRACT: This article reports the tolerance and long-term safety profiles of botulinum neurotoxin type A among Asian patients with benign essential blepharospasm (BEB) and hemifacial spasm (HFS). We performed a retrospective review of clinical documents and procedure records of consecutive BEB and HFS patients receiving onabotulinum toxin A (Botox) treatment in our clinic over the past 20 years. We reviewed the information of 105 patients diagnosed with BEB ( n = 31) and HFS ( n = 74). All of the patients were Asian. The mean age of disease onset was 59 (range 37–80) years old for BEB and 61 (range 31–83) for HFS. The mean follow up was 84 (range 12–240) months and the mean number of sessions per patient was 19 (range 1–61). The botulinum toxin dose per session increased significantly in both BEB (16.5 versus 21.6 units, p < .05) and HFS (22.6 versus 26.9 units, p < .05) patients after a mean of 18 sessions; however, the onset time, effective duration and subjective treatment outcome were similar over time in both BEB and HFS patients. At least one local complication was reported among 26% and 41% of patients with BEB and HFS respectively, with ptosis (32%) being most frequent.